EVALUATING LOCAL INNOVATION GOVERNANCE IN CIMAHI (2019–2024): TOWARD A MODEL OF INNOVATIVE LOCAL GOVERNMENT - Dicky Febriansyah Rokhmat; Widuri Wulandari (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2025)
Cimahi City is one of the local governments participating in the Innovative Government Awards (IGA) competition and has received several awards for its proposed innovations. However, the quality and quantity of innovations have slowed, remaining unchanged compared to other city governments. This study aims to evaluate innovation governance in Cimahi City from 2019 to 2024. This research employs the theory of Regional Government Innovation Design, as proposed by Irwan Noor, focusing on leadership, Organizational Climate, and Political Environment. The research employs a descriptive qualitative approach. Data collection techniques include participatory observation, interviews, and literature review. The results indicate that leadership, organizational climate, and the political environment influence each other. The regional head demonstrates a strong commitment to developing a regional apparatus capable of fostering innovation. Serious efforts are also seen in cultivating an organizational climate conducive to innovation through competitive approaches, awards, and regulations. However, there is an imbalance between the political environment of the regional head and that of the Regional People's Representative Council (DPRD) in promoting innovation at the regional apparatus level. This situation must be addressed to maintain the stability of innovation governance in Cimahi City.